Global phylogenomic novelty of the Cas1 gene from hot spring microbial communities - Salgado, Oscar; Guajardo-Leiva, Sergio; Moya-Beltrán, Ana; Barbosa, Carla; Ridley, Christina; Tamayo-Leiva, Javier; Quatrini, Raquel; Mojica, Francisco J. M.; Díez, Beatriz (Frontiers in Microbiology, 2022)
The Cas1 protein is essential for the functioning of CRISPR-Cas adaptive systems. However, despite the high prevalence of CRISPR-Cas systems in thermophilic microorganisms, few studies have investigated the occurrence and diversity of Cas1 across hot spring microbial communities. Phylogenomic analysis of 2150 Cas1 sequences recovered from 48 metagenomes representing hot springs (42-80°C, pH 6-9) from three continents, revealed similar ecological diversity of Cas1 and 16S rRNA associated with geographic location. Furthermore, phylogenetic analysis of the Cas1 sequences exposed a broad taxonomic distribution in thermophilic bacteria, with new clades of Cas1 homologs branching at the root of the tree or at the root of known clades harboring reference Cas1 types. Additionally, a new family of casposases was identified from hot springs, which further completes the evolutionary landscape of the Cas1 superfamily. This ecological study contributes new Cas1 sequences from known and novel locations worldwide, mainly focusing on under-sampled hot spring microbial mat taxa. Results herein show that circumneutral hot springs are environments harboring high diversity and novelty related to adaptive immunity systems.